A Comparative Analysis of Optimizing Leach Clustering Algorithm with Mobile Sink in WSN - Singh, I; Pooja,; Varsha, (International Journal of Computer Sciences and Engineering, 2025)
Wireless sensor networks are consisting of several sensor nodes that collect information from their surroundings and then transmit to the end user. In wireless sensor networks, the battery is the main issue. Network lifetime of network depend upon the sensor’s communication. Various methods and techniques are used to enhance the network lifetime. Some authors’ focuses on the mobile sink which is used to reduce the energy consumption. The low energy adaptive clustering hierarchy (LEACH) is an effective algorithm where all the nodes within the cluster send their respective data to the local cluster head.[1] Here, the cluster head selection is done by the technique neural network (NN) in the area of 150*150, 200*200 and 250*250, 350*350, 450*450 which provides greater functionality in the homogeneous WSNs.